Strategi Promosi Jasa Pendidikan di Pondok Pesantren Nurul Ulum Kabupaten Blitar - Nurdelima Waruwu; Zahrotul Munawwaroh; Syifa' Nurda Mu'affa (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2021)
Promotion is a marketing activity carried out by the company (school) to introduce to the public (community) about the products they have. This study aims to determine the promotion strategy through the marketing mix of educational services at the Nurul Ulum Islamic Boarding School, Blitar Regency, which is a broad unified plan for the long term and is integrated with all available resources and connects strengths, weaknesses, opportunities, and threats. This study uses a qualitative approach with a descriptive method. The data sources were selected purposively and snowball sampling. The research data was collected through interviews, observations, and document studies. Data analysis was carried out with qualitative analysis techniques which included data collection, data reduction, data presentation, and drawing conclusions. Meanwhile, to check the validity of the data, the researcher used triangulation techniques, namely data triangulation and method triangulation. The results of the research conducted by the authors show that the promotion carried out by the Nurul Ulum Islamic Boarding School in Blitar Regency has been carried out well. The implementation of the promotion strategy through the 7P mix (product, price, place, promotion, people, physical evidence, process) went quite well even though there was no planning and special program for each promotional mix activity carried out.